An Analysis of Off Record Strategies Reflecting Politeness Implicature in "Oprah Winfrey Show" - Rahma Yanti (JURNAL ARBITRER, 2017)
This thesis discusses strategies off the record that describes implicatures modesty in a conversation. Off record strategy is one of the five strategies. This strategy is discussed for the use of the language used in the forms of direct. The object of research is strategies off the record that describes implicatures politeness in a famous talk show in America, namely, "Oprah Winfrey Show". The data were taken using methods refer to refer techniques involved free conversation, where the author was not involved in the dialogue that occurs because the data is taken from the TV show, recording technique with the aid of a recorded tape. Furthermore, the authors use the technique CAAT by way of transcribing talk show back in the form transcription orthographic. This analysis uses methods equivalent pragmatic look at the role of external factors of language, especially the factor of interlocutors on selection strategies used off record. The results showed that the context of the situation and the violations of the maxim of conversation will influence the choice of strategies used off record. However, there are some cases when this option do not follow the rules. This is because of other factors that come into play in a conversation such as an intonation. implicatures appear generally in the form of affirmation that is used in polite. In one sentence found two or more strategy off record selected speakers. Keyword:Â off record strategy, implicature, implicatures,Â politeness